PRONUNCIATION PRACTICE EXPERIMENT USING ENGLISH LANGUAGE SPEECH ASSISTANT (ELSA) APPLICATION AS A LEARNING MEDIA - Hidayah, Nadya; Hadi, Muhamad Sofian; Islah, Nurul (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2024)
The purpose of this article is to prove the effectiveness of the ELSA application in improving students’ pronunciation ability. The researcher used the quantitative method using a pre-experimental design. The pre-experimental design was used to provide an answer to this problem. In collecting the data, the researcher used pre-tests and post-tests. In this study, there is only one experimental group which is grade 8.5 at public junior high school 13 Jakarta which consists of 36 students. The experimental group took a pre-test to measure their ability in English pronunciation before starting the treatment. T-test is used to assess whether there is a significant difference between the scores of one group before and after the treatment. Based on the results of the students' pre-test and post-tests, the pre-test had an average score of 68.78 and the post-test had an average score of 80.08. In analyzing the data, the researcher used the SPSS 25 version, which shows that the T-Test value was higher than T-Table (15.770 > 2.030). It proved that the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. It can be concluded that the ELSA application is an effective learning media for improving students' pronunciation ability.